2021
DOI: 10.1021/acs.joc.1c01762
|View full text |Cite
|
Sign up to set email alerts
|

Controllable Synthesis of Two Isomers 4H-Chromene and 2,8-Dioxabicyclo[3.3.1]nonane Derivatives under Catalyst-Free Conditions

Abstract: A one-pot method for the selective synthesis of two isomers 4H-chromene and 2,8-dioxabicyclo[3.3.1]­nonane derivatives was developed without a catalyst and using EtOH/H2O (4:1, v/v) as the solvent. The reaction was conducted under mild conditions, with forming multiple chemical bonds in one pot and high atom economy, and only a stoichiometric amount of H2O is produced as the byproduct. Its selectivity was controlled by thermodynamics and kinetics, and the reasons for the transformation of the two structures ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…Then, the influence of reaction temperature and time on this transformation was screened. The results indicated that TfOH (10 mol%) as the catalyst under the solvent-free condition at 120 °C was demonstrated to be the optimized parameters (Table 1, entries [8][9][10][11]. Interestingly, cyclohexanedione-fused 2,8-dioxa bicyclo[3.3.1]nonane 4 a was exclusively obtained when the solvents were screened while cyclohexanedionefused 2,8-oxaza bicyclo[3.3.1]nonane 3 a was not detected, and toluene was demonstrated as the best reaction medium (Table 1, entries [12][13][14][15][16][17].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Then, the influence of reaction temperature and time on this transformation was screened. The results indicated that TfOH (10 mol%) as the catalyst under the solvent-free condition at 120 °C was demonstrated to be the optimized parameters (Table 1, entries [8][9][10][11]. Interestingly, cyclohexanedione-fused 2,8-dioxa bicyclo[3.3.1]nonane 4 a was exclusively obtained when the solvents were screened while cyclohexanedionefused 2,8-oxaza bicyclo[3.3.1]nonane 3 a was not detected, and toluene was demonstrated as the best reaction medium (Table 1, entries [12][13][14][15][16][17].…”
Section: Resultsmentioning
confidence: 99%
“…[7] Recently, 4Hchromene and 2,8-dioxabicyclo [3.3.1]nonane derivatives have been synthesized by kinetic control in a mild conditions. [8] To continue our interest in switchable synthesis from functionalized synthons, [9] we envisioned that 3-amino-2-cyclohexene-1-one as dinucleophiles reacting with 2-hydroxychalcones for the synthesis of heterocyclics appeared promising, since 3-amino-2-cyclohexene-1-one has emerged as valuable synthons in numerous important chemical transformations. [10] Due to the difference in activity between 5,5-dimethylcyclohexane-1,3-dione and 3-amino-2-cyclohexene-1-one, we introduced Brønsted acid as catalyst to accelerate the reaction rate and improve the yield.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…demonstrated a one‐pot catalyst‐free and green synthesis of functionalized 4 H ‐chromenes 162 via a tandem reaction from o ‐hydroxy chalcones 67 and 1,3‐cyclohexidikeones 161 (Scheme 41). [39] The high efficiency of this reaction was reflected in simultaneous formation of three C−C bonds and one C−O bond under catalyst‐free conditions within only 4–6 h. The use of EtOH/H 2 O as solvent proved its greenness for access to 4‐alkyl 4 H ‐chromenes.…”
Section: Tandem Michael Addition/cyclization/dehydration From 2‐hydro...mentioning
confidence: 98%